Identification of novel anti-tumor peptides from enzymatic hydrolysis of soy-based tempeh and their mechanism in pancreatic and colorectal cancer cells - Kiki Lukman; Prapanca Nugraha; Nurpudji Astuti Taslim; Nuril Farid Abshori; Elvan Wiyarta; Timothy Sahala Gerardo; Krisanto Tanjaya; Juan Leonardo; Raymond Rubianto Tjandrawinata; Happy Kurnia Permatasari; Fahrul Nurkolis (Journal of Agriculture and Food Research)
The aim of this work was to identify peptides in a hydrolysate of soy-based tempeh (SBTE), and determine their antitumor function using bioinformatics and mode cells. The work employed a multi-faceted approach to determine the antitumor activity of SBTE and its derived peptide components against pancreatic and colorectal cancer cells. The soy-based tempeh was hydrolyzed with trypsin, followed by metabolic analysis to identify a new peptide P1 (GENEEEDSGAIVTVK) together with four dipeptides. A network pharmacology analysis allowed the identification of 140 genes and proteins related to colorectal and pancreatic cancer that target of the tempeh peptides. from key receptors involved in cancer signaling, particularly colorectal and pancreatic cancers. Major interactions included the renin-angiotensin system, apoptosis-multiple species, microRNAs in cancer, and cytokine signaling pathways. The dipeptides exhibited strong binging with cancer receptors such Poly (ADP-ribose) polymerases 1 (PARP1, ΔG -6.5 kcal/mol) and epidermal growth factor (EGFR, ΔG -6.2 kcal/mol). In the PANC-1 pancreatic and HT-29 colon cells, the hydrolysate and the peptides downregulated by 10-fold the expression for five cancer receptors namely EGFR, iNOS, BIRC2, ANPEP, and PARP1. This research provides new insights into the properties of tempeh peptides, which could lead to the development of functional foods or new drugs for anticancer therapy.